2011
DOI: 10.1007/s00425-011-1414-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of multiple aquaporin genes in Arabidopsis by a pair of recently duplicated DREB transcription factors

Abstract: Identifying the transcription factors that mediate responses to abiotic stress is of fundamental importance in plant biology, not least because of their potential utility in crop improvement. The recently duplicated genes RAP2.4B and RAP2.4 encode transcription factors belonging to the abiotic stress-associated DREB A-6 clade in Arabidopsis thaliana. Both proteins localise exclusively to nuclei and show similar DRE-element-binding characteristics. Expression analysis of stressed and non-stressed plants reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 64 publications
(84 reference statements)
2
51
0
Order By: Relevance
“…It has been documented that the capability to cold acclimatize is associated with definite signal transduction pathways ensuring in the commencement of numerous cold-regulated (COR) genes that develop tolerance in plants (Castonguay et al, 2013). C-repeat binding factors (CBF/DREB) have been reported in previous studies to induce the expression of a group of genes related to increased stress tolerance (Wisniewski et al, 2011;Yang et al, 2011;Rae et al, 2011). The subfamily DREB can be divided into further six small classes termed as A-1 to A-6 (Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that the capability to cold acclimatize is associated with definite signal transduction pathways ensuring in the commencement of numerous cold-regulated (COR) genes that develop tolerance in plants (Castonguay et al, 2013). C-repeat binding factors (CBF/DREB) have been reported in previous studies to induce the expression of a group of genes related to increased stress tolerance (Wisniewski et al, 2011;Yang et al, 2011;Rae et al, 2011). The subfamily DREB can be divided into further six small classes termed as A-1 to A-6 (Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ERN1 and ERN2 possess both specific and overlapping expression profiles during rhizobial infection. A number of other closely related TFs also display specific and overlapping expression patterns during different developmental processes (AP2 TFs [Chandler et al, 2007;Rae et al, 2011] and NAC TFs [Mitsuda and Ohme-Takagi, 2008]). Such finetuned regulation is generally associated with both redundant and specific functions of the respective TFs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the abundance of RAP2.4 protein was regulated by a BR-C, ttk and bab/Pox virus Zinc finger (BTP/POZ-MATH) or briefly known as BPM protein family (Weber & Hellmann, 2009). In addition, it is suggested that this gene plays a role in the regulation of water homeostasis (Rae et al, 2011). The HbERF-Ib7 gene is a GEM in response to latex harvesting stress but it has no known ortholog in Arabidopsis.…”
Section: Identification Of Ap2/erf Gene Expression Markers Related Wimentioning
confidence: 99%